The Relationship Between XBRL Adoption and CSR Disclosure Transparency in Companies Listed on The Indonesia Stock Exchange - Tarigan, Rony; Se Tin, Se Tin (Jurnal Akuntansi, 2025)
Purpose – This study aims to analyze the relationship between the implementation of eXtensible Business Reporting Language (XBRL) and the transparency of Corporate Social Responsibility (CSR) disclosures in companies listed on the Indonesia Stock Exchange. The research is based on the frameworks of Stakeholder Theory and Legitimacy Theory, which serve as the foundation for assessing structured non-financial reporting practices. Design/Methodology/Approach – A quantitative explanatory approach was applied to investigate the relationships between variables in the research model. Data were collected through a survey involving 75 respondents responsible for sustainability reporting in public companies familiar with the use of XBRL. The sampling technique employed was purposive sampling, with selection criteria focusing on individuals directly involved in preparing CSR reports and digital company documents. The instrument consisted of 25 indicators derived from prior studies. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. Findings – The results indicate that XBRL adoption significantly and positively affects CSR transparency (β = 0.879; R² = 0.772). This finding demonstrates thatXBRL serves not only as a technical reporting tool but also as a strategic instrument for enhancing the transparency, comparability, and reliability of nonfinancial disclosures. Research limitations/Implications – The study is limited to public companies already familiar with the XBRL system. Future research is encouraged to consider additional factors such as technological readiness and regulatory pressures. These findings highlight the need for a national XBRL-based CSR taxonomy and integration of digital sustainability reporting into regulatory platforms such as OJK’s SPE system. Keywords: CSR, Digital Reporting, Information Transparency, XBRL